Risk factors for methicillin-resistant Staphylococcus aureus colonization in a level-IV neonatal intensive care unit: a retrospective study - Julia Elzbieta Galuszka; Kim Thomsen; Jenny Dahl Knudsen; Rikke Louise Stenkjaer; Rikke Nielsen; Karen Leth Nielsen; Andreas Petersen; Barbara Juliane Holzknecht; Mette Damkjaer Bartels; Morten Breindahl; Lise Aunsholt (Cambridge University Press, 2023)
Abstract Objective: To identify risk factors associated with methicillin-resistant Staphylococcus aureus (MRSA) colonization in neonatal patients during an MRSA outbreak to minimize future outbreaks. Design: Retrospective case-control study. Setting: Level-IV neonatal intensive care unit (NICU) at Copenhagen University Hospital, Rigshospitalet, Denmark. Patients: Neonates with either MRSA or methicillin-susceptible Staphylococcus aureus (MSSA) Methods: Methicillin-resistant Staphylococcus aureus-positive neonates were matched with those colonized or infected with MSSA in a 1:1 ratio. The control group was selected from clinical samples, whereas MRSA-positive neonates were identified from clinical samples or from screening. A total of 140 characteristics were investigated to identify risk factors associated with MRSA acquisition. The characteristics were categorized into three categories: patient, unit, and microbiological characteristics. Results: Out of 1,102 neonates screened for MRSA, between December 2019 and January 2022, 33 were MRSA positive. They were all colonized with an MRSA outbreak clone (spa type t127) and were included in this study. Four patients (12%) had severe infection. Admission due to respiratory diseases, need for intubation, need for peripheral venous catheters, admission to shared rooms with shared toilets and bath facilities in the aisles, and need for readmission were all correlated with later MRSA colonization (P < 0.05). Conclusion: We identified clinically relevant diseases, procedures, and facilities that predispose patients to potentially life-threatening MRSA infections. A specific MRSA reservoir remains unidentified; however, these findings have contributed to crucial changes in our NICU to reduce the number of MRSA infections and future outbreaks.